Electrochemical Reduction of p-Hydroxyphencyl Bromide - Rao, K.M.; Nageswara Rao, P.; Reddy, S.J.; Adinarayana Reddy, K. (Asian Journal of Chemistry, 2010)
The electrochemical reduction of carbon-bromine bond in p-hydroxyphenacyl bromide has been studied employing Differential pulse polarographic and cyclic voltammetric techniques in 40% (v/v) ethanolwater mixture in a suitable pH range from 5.5 to 10.0. The effect of solvent and the nuclear substitution on the reduction rate constant values are evaluated and reported. The possible electrochemical reduction mechanism is proposed.